2009
DOI: 10.4103/0378-6323.55391
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of plant sensitivity among patients of photodermatoses: A control-matched study of 156 cases from new delhi

Abstract: This study indicates that parthenium (and possibly xanthium) may act as important environmental factors in the initiation and perpetuation of not only ABCD but of CAD as well. Photoexacerbation to UVA at positive parthenium/xanthium sensitivity sites in ABCD and CAD indicates that ABCD with photosensitivity to compositae can lead to CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In a study done by Kar et al ., it was observed that parthenium plays a significant role in the initiation and spread of air borne contact dermatitis and chronic actinic dermatitis (CAD). [ 12 ] A 20-year analysis of antigens causing photoallergic contact dermatitis done in New York showed 11.6% positivity to plant derivatives including sesquiterpene lactone mix. [ 13 ] The coexistence of allergic contact dermatitis (ACD) with CAD is well known.…”
Section: Discussionmentioning
confidence: 99%
“…In a study done by Kar et al ., it was observed that parthenium plays a significant role in the initiation and spread of air borne contact dermatitis and chronic actinic dermatitis (CAD). [ 12 ] A 20-year analysis of antigens causing photoallergic contact dermatitis done in New York showed 11.6% positivity to plant derivatives including sesquiterpene lactone mix. [ 13 ] The coexistence of allergic contact dermatitis (ACD) with CAD is well known.…”
Section: Discussionmentioning
confidence: 99%
“…However, Kar et al in their study have noted that Parthenium plays an important role in the initiation and perpetuation of airborne contact dermatitis (ABCD) and CAD. [22] Similarly, Somani has also reported photoallergy to Parthenium. [18] Thus, these agents and particularly the oleoresins from Compositae plants might play a role in inducing the photoaggravation of CAD.…”
Section: Clinical Featuresmentioning
confidence: 94%
“…However, it should be emphasized to all that avoidance of further exposure can lead to recovery from dermatitis in many cases (5). The rapid growth of parthenium weed in India and its ill effects on the population makes it important to detect all cases of parthenium dermatitis (8). Patch testing is a definitive tool for diagnosing ABCD (9).…”
Section: Fig 2: Lichenification and Excoriation Over Armsmentioning
confidence: 99%